Frequency of Sportive Injuries in Amateur Athletes and Factors Affecting Injuries - Arif Satıcı; Osman İmamoğlu; Egemen Ermiş (Türk Spor ve Egzersiz Dergisi)
ABSTRACTIt is possible to face injury risk whether the sport is recreational or contest purpose based. Exposure to injury can be attributed to many factors (field, competitor, etc.). Because of an injury amateur or elite athletes may move away from their sporting lives. This study aims to investigate frequency of sport injuries and factors affecting injuries to amateur athletes in Samsun region.666 amateur athletes serving in various amateur sports clubs in Samsun province were selected randomly. 462 participants were men, 204 were women. 240 athletes in individual sports branches (wrestling, table tennis, taekwondo, wrist wrestling, wushu, athletics), and 426 athletes in team sports (basketball, football, handball, volleyball) constitute the sample. The subjects completed a sports injury survey developed by the researchers. X2 was used for statistical analysis of the data.Participants were most often (44.6%) faced with a sprain injury. The most injured areas were the wrists and ankles, with a ratio of 36.4%. The period of disability was found to be 0-1 days with 62.8%. The injured rested for 7 days or less with a ratio of 57.4%. Athletes were found to exercise partially intensively during injury (52.1%). Treatment applied during injury was mostly performed by the self, the doctor and others. Among the causes of injuries, opponent player was found to be the leading factor with 33.6%.ddition, medical personnel can be provided to amateur sports clubs with the support of the state.